The Assessment of Hordein Variability in Czech Spring Barley Varieties - Bradová, Jana; Psota, Vratislav (KVASNY PRUMYSL, 2017)
The allele variability of the hordein controlled by Hrd A, Hrd B, and Hrd F loci was investigated in Czech spring barley varieties using starch gel electrophoresis. The studied set included landraces, old varieties and modern varieties. A total of 34 hordein alleles were detected in the set of 70 barley varieties. Identifi ed hordein alleles created totally 43 electrophoretic patterns. Hordein allelic variability of the complete set expressed as an index of genetic variability (H) was 0.941. The genetic variability index (H) of modern barley varieties was 0.946 while in landraces and old varieties on average lower variability was recorded H=0.870. On the contrary, landraces and old varieties were characterized by much higher intra-varietal polymorphism than modern varieties.